Implementation of the Principle of Legal Certainty in Implementation of the State Administrative Court Decision - Soeleman Djaiz Baranyanan (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
The implementation of the State Administrative Court's decision is a crucial element in upholding the rule of law in the field of state administration. However, the practice often faces obstacles such as non-compliance of State Administrative officials and limitations of execution mechanisms. This study analyzes juridically the procedure for implementing the decision of the State Administrative Court based on Law Number 51 of 2009 concerning the State Administrative Court, focusing on obstacles and potential solutions. This study uses a normative approach with doctrinal analysis and case studies, the results of the study show that automatic execution and strengthening of administrative sanctions are necessary to ensure legal certainty.This study examines the implementation of the principle of legal certainty in the implementation of the decisions of the State Administrative Court in Indonesia. Although the State Administrative Court's decision has binding legal force, challenges in its implementation often erode legal certainty for justice seekers. This article analyzes the legal framework that governs the implementation of the State Administrative Court's rulings, identifies the factors that hinder the certainty of implementation, and offers juridical and institutional solutions to strengthen the implementation of the principle of legal certainty. Using normative legal research methods supported by empirical data from decisions and execution practices, this study argues that regulatory reformulation and strengthening external supervision are crucial to ensure legal certainty and effectiveness of the State Administrative Court.